Slave systems ancient and modern - Dal Lago, Enrico 1966-; Katsari, Constantina 1972- (Cambridge University Press, 2008)
A ground-breaking edited collection charting the rise and fall of forms of unfree labour in the ancient Mediterranean and in the modern Atlantic, employing the methodology of comparative history. The eleven chapters in the book deal with conceptual issues and different approaches to historical comparison, and include specific case-studies ranging from the ancient forms of slavery of classical Greece and of the Roman empire to the modern examples of slavery that characterised the Caribbean, Latin America and the United States. The results demonstrate both how much the modern world has inherited from the ancient in regard to ideology and practice of slavery; and also how many of the issues and problems related to the latter seem to have been fundamentally similar across time and space